HOW TRUST, RISK TOWARD ATTITUDE WHEN SHOPPING RETAIL ONLINE - Suleman, Dede; Dedi Suharyadi; Sri Rusiyati; Sabil; Dinar Riftiasari; Sofyan Marwansyah (Dinasti Publisher, 2020)
This study aims to analyze the relationship between trust and risk of shopping decisions at online retail. This study uses a sampling quota sampling technique with a survey method with a total sample of 100 respondents from the city of Jakarta with the criteria of respondents aged over 18 years and have purchased products online. The results of the study stated that trust influences consumer attitudes. While the risk was not influence on consumer attitudes in shopping online. the results of this study can be a reference for further research.